Neurological and Psychiatric Sequelae of Developmental Exposure to Antiepileptic Drugs - Meador, Kimford; Gedzelman, Evan (Frontiers in Neurology, 2012)
The neurons in the developing mammalian brain are susceptible to antiepileptic drug (AED) effects. It is known that later in life deficits in cognitive performance as well as psychiatric deficits can manifest after early AED exposure. The extent of these deficits will be addressed. This review will attempt to draw parallels between the existent animal models and human studies. Through analysis of these studies, important future research will be elucidated and possible new and emerging therapies will be discussed.